Molecular genetic aspects of prostate cancer radioresistance - E. P. Omelchuk; D. S. Kutilin; S. N. Dimitriadi; M. A. Gusarev; N. N. Timoshkina (Бюллетень сибирской медицины, 2021)
Radioresistance of prostate cancer is a complex therapeutic problem. Biochemical recurrence after radiation therapy occurs in 22–69% of patients with prostate cancer. Nearly half of these patients progress to a clinical relapse within 15 years, and a third progress to castration-resistant prostate cancer. This review analyzes literature data on radioresistance mechanisms in prostate cancer cells. We searched for literature published in eLibrary, PubMed, and Scopus databases by key words: prostate cancer, radioresistance, markers. In total, 568 foreign and 178 national articles published between 1975 and 2020 were found. Of these publications, 77 articles were selected (published in 2001–2020), which reveal the molecular basis of tumor radioresistance.Modern understanding of the origin of radioresistant cancer cells focuses on processes leading to enhanced DNA repair, activation of anti-apoptotic signaling pathways, and a decrease in the level of endogenous and exogenous reactive oxygen species. The state of a tumor microenvironment, autophagy, and epithelial-mesenchymal transition also play an important role in radioresistance. Currently, the mechanisms of resistance to radiation therapy are explained by the existence of tumor stem cells, which provide genetic heterogeneity and activation of carcinogenesis signaling pathways. The tumor can also be protected from radiation by a hypoxic microenvironment. Since cancer stem cells can acquire plasticity in response to radiation therapy, search for markers of radioresistance for screening and identification of radioresistant prostate cancer is relevant.